'Unheard voices’: Perceptions of women with mental illness on nurses screening routinely for domestic violence: A qualitative analysis - Poreddi, Vijayalakshmi; Reddy, S. Sai Nikhil; Gandhi, Sailaxmi; P, Marimuthu; BadaMath, Suresh (Investigación y Educación en Enfermería, 2021)
Objective. To explore women's experiences of violence and their opinion on routine screening for domestic violence by nursing professionals in mental health care settings. Methods. This qualitative narrative research design was carried out among 20 asymptomatic women with mental illness at a tertiary care centre in Bangalore, India. Results. Narrative content analysis was performed, and five dominant themes have emerged: 1. Understanding the nature and signs of violence (subtheme: Meaning of violence), 2. Abusive experiences of women with mental illness (subthemes: Physical violence, psychological violence, social violence, sexual violence and financial violence), 3. Experiences on disclosure of violence (subthemes: Identification of violence by nursing professionals, Experiences of disclosure of violence), 4. Barriers for disclosure of abuse(subthemes: Fear of consequences, the hectic schedule of nursing staff, helplessness and hopelessness, perceived poor family support). 5.Routine screening for violence by nursing professionals (subthemes: reasons for routine inquiry of violence, nature of inquiry by the nursing professionals). Conclusion. Women with mental illness were undergoing more than one form of violence, and most of the participants supported routine screening by nursing professionals. Nurses play an essential role in identifying and supporting abused women in mental health care settings.